The Investigation Of The UK Role In The Indo – Pacific Region - Benkhalifa Amani; Bouallaga Intissar (University of Eloued جامعة الوادي, 2025)
The UK’s interest in the Indo-Pacific is part of an overall strategic repivot in a post-Brexit policy, of which the 2021 Conservative government’s proposal – the Indo-Pacific tilt – is of key significance. Historically, the UK has been a Euro-Atlantic nation, and in the Brexit era, it has been looking to reconfigure itself in an international order context under a substantive geopolitical category. This dissertation considers the changing contours of the UK’s political-economic-security engagement with the Indo-Pacific region amidst the reconfiguration of global and regional power realities. Adhering to its classic diplomacy identity, the UK’s return to the area is informed by practical responses to contemporary demands, including shifting global economic scenarios (triggered by China’s rise), multilateral economic cooperation, and strategic defence grouping. Qualitative inquiry for four case studies is employed to enrich the conclusive findings. Using a descriptive-analytical approach, the study draws upon primary data collected from government documents and policy reports. It is supported with secondary data obtained from scholarly published research. The findings suggest that Britain’s new Indo-Pacific strategy is not simply a continuation of historical influence but a nuanced rebalancing process influenced by legacy interests alongside adaptive policymaking appropriate for a more multipolar world. In this rebalance, the UK is a key technologically advanced partner whose role is central to regional security and stability. يُمثل اهتمام المملكة المتحدة بمنطقة المحيطين الهندي والهادئ جزءًا من إعادة نظر استراتيجية شاملة في عالم ما بعد خروج بريطانيا من الاتحاد الأوروبي، وتُعدّ هذه المنطقة محوريةً فيها. لطالما كانت المملكة المتحدة دولةً أوروبيةً أطلسية، وفي حقبة خروجها من الاتحاد الأوروبي، تسعى إلى إعادة هيكلة نفسها في سياق النظام الدولي ضمن إطار جيوسياسي جوهري. تتناول هذه الأطروحة الملامح المتغيرة لانخراط المملكة المتحدة السياسي والاقتصادي والأمني ​​في منطقة المحيطين الهندي والهادئ في ظلّ إعادة تشكيل واقع القوة العالمية والإقليمية. وانطلاقًا من هويتها الدبلوماسية التقليدية، فإن عودة المملكة المتحدة إلى المنطقة تستند إلى استجابات عملية للمطالب المعاصرة، بما في ذلك السيناريوهات الاقتصادية العالمية المتغيرة (الناجمة عن صعود الصين)، والتعاون الاقتصادي متعدد الأطراف، بالإضافة إلى التجمع الدفاعي الاستراتيجي. وقد استُخدم البحث النوعي لأربع دراسات حالة لإثراء التحليل. وباستخدام نهج وصفي تحليلي، تعتمد الدراسة على بيانات ثانوية جُمعت من وثائق حكومية، وتقارير سياسات، وأدبيات منشورة أكاديميًا. وتشير الاستنتاجات إلى أن الاستراتيجية البريطانية الجديدة تجاه منطقة المحيطين الهندي والهادئ ليست مجرد استمرار للتأثير التاريخي، بل هي عملية إعادة توازن دقيقة تتأثر بالمصالح القديمة إلى جانب صنع السياسات التكيفية المناسبة لعالم أكثر تعددًا للأقطاب.
Master's Degree In Literature and Civilization
Keywords: Indo-Pacific; Indo-Pacific tilt; post-Brexit policy; UK’s engagement; المحيطان الهندي والهادئ، الميل نحو المحيطين الهندي والهادئ، سياسة ما بعد خروج بريطانيا من الاتحاد الأوروبي، مشاركة المملكة المتحدة.